Adenylate cyclase 5 is required for melanophore and male pattern development in the guppy (Poecilia reticulata). (17th July 2015) - Kottler, Verena A.; Künstner, Axel; Koch, Iris; Flötenmeyer, Matthias; Langenecker, Tobias; Hoffmann, Margarete; Sharma, Eshita; Weigel, Detlef; Dreyer, Christine
Summary: Guppies ( Poecilia reticulata ) are colorful fish that have attracted the attention of pigmentation researchers for almost a century. Here, we report that the blond phenotype of the guppy is caused by a spontaneous mutation in the guppy ortholog of adenylate cyclase 5 ( adcy5 ). Using double digest restriction site‐associated DNA sequencing (ddRADseq) and quantitative trait locus (QTL) mapping, we linked the blond phenotype to a candidate region of 118 kb, in which we subsequently identified a 2‐bp deletion in adcy5 that alters splicing and leads to a premature stop codon. We show that adcy5, which affects life span and melanoma growth in mouse, is required for melanophore development and formation of male orange pigmentation traits in the guppy. We find that some components of the male orange pattern are particularly sensitive to loss of Adcy5 function. Our work thus reveals a function for Adcy5 in patterning of fish color ornaments.